Improving Student Learning Outcomes On The Theme Health Is Important Content Of Science Learning Through Image Media - Juariah, Siti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this research is the answer that will be examined in research. This study aims to improve student learning outcomes of Natural Sciences learning content through the media of images in fifth grade students of SD N 1 Tambak in the 2021/2022 academic year. This research was conducted in 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. The research subjects were teachers, 6 male students, and 1 female student. Data collection techniques used are observation and tests in the form of formative tests. The results showed that there was an increase in students' understanding, teacher skills, and students' abilities in each cycle. Student activity in science learning using media images cycle 1 with sufficient criteria, increased in cycle II with good criteria. Mastery learning in cycle 1 of the learning outcomes of 62.5%, namely 2 of 7 students with an average value of 74, while in cycle II mastery increased to 100% or 7 of students with an average value of 85. The conclusion of this research is that by using Image media can improve student learning outcomes so that it has an impact on increasing the ability to understand implementing healthy living for class V SD N 1 Tambak